Lixiviação dos íons nitrato e potássio em latossolo submetido à aplicação de diferentes doses e tipos vinhaça - Godoy, Fabiane Karen (Universidade Federal de São Carlos, 2013)
Vinasse is a liquid effluent with a high organic load and it has significant concentrations of Nitrate (NO3 -) and Potassium (K⁺). It is of great interest for the sugarcane sector by reducing costs in fertilizer application. According to the technical regulation P4.231 of CETESB, the impasse in the usage of vinasse in fertigation leads the search toward new alternatives for the effluent usage and treatment. This study investigated the mobility of NO₃ and K⁺ at different depths of Oxisol and the changes in soil electrical conductivity (ECs) in the layer next to the water table. Additionally, this work evaluated whether the rate and period of vinasse application established by the technical regulation P4.231 are appropriate to minimize the risk of soil and groundwater contamination, also evaluate the residual effects of vinasse in soil columns after 6 months monitoring, in order to contribute to the improvement of P4.231. The study was conducted in 15 x 170 cm PVC columns (diameter x height). The column packing was done in order to reproduce the profile of Oxisol, mainly on the thickness and density of the layers collected. Extractors of soil solution were installed at depths of 50 cm and 100 cm from the top of the columns. In the base of the column, a drain was placed at 50 cm to collect the leached. TDR (Time Domain Reflectometer) probes were installed at 120 cm to monitor soil moisture and ECs. After 15 days of saturation with distilled water, the columns received the application of vinasse in nature (V), vinasse in nature subjected to chemical treatment (Q), vinasse in nature subjected to biological treatment (B) and concentrated vinasse (C) at dose calculated by the P4.231 (1) and at duplicated dose calculated (2). The columns were subjected to a simulated rainfall based on the behavior of the rainfall in the region of Araras, SP. After collecting the solution at 50 and 100 cm and leached at 150 cm, determinations of NO3 - contents, by the method of brucine, and K+, by flame photometry, were made every 15 days for 5 months. Significant differences were observed in the levels of NO3 - and K+ in solution attributed to time, depth, type and dose of vinasse. After 45 days of the application of V1, V2, Q1, Q2, B1, B2 vinasses, the NO3 - had leached through the layer until 100 cm. The adsorption of NO3 - , which occurred in the layer until 100 cm, delayed but not prevented ion leaching to a deeper layers than 100 cm, from the 90 days, independent of the type and dose of vinasse. All vinasses, after 105 days, resulted in levels of NO3 - from 3 to 4 times greater than the maximum allowed value for the quality of groundwater (10 mg L-1). At the layer until 50 cm, all the vinasses promoted changes in the K+ solution after 30 days of application, but the application of Q2, C1, C2, and specifically B2, resulted in higher rate of K+ solution. In the layer until 50 cm, a decrease in the levels of K+ in solution was observed from 90 days. Unlike what happened with NO3 -, K+ was absorbed by surface soil layers and its leaching was avoided. Regardless of the type and dose of vinasse, there was an increase in ECs until the 15th week after application, without compromising the quality of the water. The application of vinasses in nature treated chemically and biologically resulted in higher values of ECs. The use of vinasse in nature, at the rate calculated by P4.231, resulted in lower values of NO3 - and K+ in solution, regardless of depth, thus it is recommended that the standard P4.231 should be used only for the application of vinasse in nature. It is suitable to incorporate the levels of NO3 - in the equation in order to calculate the dose of vinasse by P4.231, since the NO3 - had reached the layer at 100 cm in 45 days, i.e., an incompatible period of time with the adequate development of the sugarcane root system, allowing the leaching of NO3 - out of the root zone of influence. In general through the analysis of soil column percolation after 6 months of monitoring, it was possible to verify a residual effect of vinasse, considering all types and doses, in soil samples for the parameters Na+, K+ , and Fe3+. The K+ was retained in the 0 to 50 cm in the percolation columns. Conversely Na+, showed the highest concentrations in the depths of 80-130 cm, showing their greatest potential leaching compared to K+.
Leaching of nitrate and potassium ions in oxisol subjected to different doses and types of vinasse
Keywords: Vinhaça; Adsorção; Setor sucroenergético; Resíduo agroindustrial; Lixiviação; Solo tropical; NO3 -; K+; Leaching; Adsorption; Sugarcane industry; Tropical soil; Agroindustrial residue; CIENCIAS AGRARIAS